PENGEMBANGAN LEMBAR KERJA SISWA MATERI SUHU DAN KALOR BERBASIS SCIENTIFIC METHOD UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - Fitri Savitri; Agus Setyo Budi; Mangasi Alion Marpaung (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
The purpose of this study is to develop a student’s worksheets based on scientific method as one of the supporters in laboratory, especially on the material temperature and heat can increase the science process skills. The research was conducted at SMAN 22 Jakarta Timur by comparing two classes of grade X as experimental and control class. This research used ADDIE approach to analyze, design, development, implement and evaluation the worksheet. Worksheet feasibility test results based on scientific method has been validated by experts for material and media, also validated by the user. The result of media experts are 80.96%, from material experts are 89.83% and the result of user are 83.16% from teachers and 82.88% from students. The worksheet that was validated then used to collect the data from experimental and control class. The average percentage of all aspects of science process skills increased by 11.66%. Therefore, it can be concluded that the overall worksheet based on scientific method can improve high school student’s science process skills. Keywords: R&D, ADDIE, Worksheet, Scientific Method, Science Process Skill.